The Relationship Between Sarbanes–Oxley Policies and Donor Advisories in Nonprofit Organizations - Saxton, Gregory D. (Journal of business ethics, 2019)
This study examines the impact of Sarbanes–Oxley (SOX) on the nonprofit sector. Focusing on three key SOX policies applicable to charities—conflict-of-interest policies, records retention policies, and whistleblower policies—this study tests the relationship between the existence and addition of these policies on subsequent ethical and governance lapses as reflected in the issuance of “donor advisories” by the large third-party ratings agency Charity Navigator. The findings suggest that, controlling for other relevant organizational factors, the three SOX-inspired written policies are related to a reduced likelihood of donor advisories in the organizations rated by Charity Navigator.